Prognostic value of depression severity indicators for determining clinical outcomes of sleeve gastrectomy in patients with obesity - V.V. Skyba; O.V. Ivanko; I.I. Pliuta (Mìžnarodnij Endokrinologìčnij Žurnal, 2025)
Background. Sleeve gastrectomy is an effective treatment for obesity with positive impact on patients’ physical and mental health components. However, the influence of bariatric intervention on mental state is complex and insufficiently studied. The aim of the study was to characterize the prognostic value of depression severity indicators for determining clinical outcomes of sleeve gastrectomy in patients with obesity. Materials and methods. Clinical outcomes of 93 patients with obesity who underwent sleeve gastrectomy were analyzed. The group included 69 (74.19 %) women and 24 (25.81 %) men. Their average age was 42.20 ± 11.09 years. The mean body mass index at initial presentation was 46.23 ± 7.65 kg/m2. Clinical outcomes were determined according to the SF-BARI QoL. Depression severity was assessed using the PHQ-9 questionnaire. Results. The mean clinical outcome of sleeve gastrectomy in the long-term treatment period was 129.77 ± 28.07 points, corresponding to very good values. Excellent treatment results were found in 29 (31.18 %) patients, very good in 38 (40.86 %), good in 20 (21.51 %), and satisfactory in 6 (6.45 %) subjects. The mean total depression severity score was 7.10 ± 7.57 points, indicating mild depression. No signs of depression were found in 15 (16.13 %) subjects, while 40 (43.01 %) showed minimal symptoms. Mild depression was detected in 10 (10.75 %) people, moderate in 9 (9.68 %), moderate-to-severe depression in 13 (13.98 %), and severe depression in 6 (6.45 %) patients. Increased depression symptoms were associated with significantly worse sleeve gastrectomy results (τ = –0.74, p < 0.00001). The absence of depression was associated with significantly higher chances of excellent treatment outcomes (odds ratio (OR) = 27.30, confidence interval (CI) (5.44–137.02), p = 0.0000004). Higher chances of very good clinical indicators were recorded in patients with minimal (OR = 12.89, CI (4.69–35.44), p ≤ 0.00000001), moderate (OR = 17.50, CI (3.21–95.37), p = 0.0002), and moderate-to-severe depression (OR = 94.67, CI (10.66–840.77), p ≤ 0.00000001). The presence of severe depression was associated with satisfactory results of bariatric intervention in the long-term postoperative period (OR = 430.00, CI (22.40–8254.17), p = 0.0000001). Conclusions. The study confirmed the high clinical efficacy of sleeve gastrectomy in treating patients with obesity. It was found that the presence of depression, particularly moderate, moderate-to-severe, and severe, was associated with worse clinical outcomes of bariatric intervention in the long-term postoperative period.